Correlates of Physical Activity in Asian Adolescents: A Literature Review - Hidayati, Husna; Hatthakit, Urai; Isaramalai, Sang-Arun (Nurse Media Journal of Nursing, 2012)
Background: Physical activity is important to prevent several chronic diseases in adulthood. Nowadays, young people do not regularly perform physical activity. Several factors may influence their decision. Most of studies were conducted in western countries. However the findings might not be generalized regarding the differences in culture and social condition. Therefore, reviewing the correlates of physical activity among adolescents in Asian countries is essential. Purpose: To update the state of knowledge on factors associated with adolescents’ physical activity in Asian countries. Methods: Literature review on existing articles retrieved from electronic databases was conducted. The review on factors of physical activity was set based on the setting of study, adolescents as participants of the study and the year of publication ranged from 2002-2011. Result: The findings compiled the evidence of relationships between physical activity and several influencing factors. Intrapersonal factors age, gender, socioeconomic status, parental education, and perceptions related to physical activity- perceived self efficacy, perceived benefits, and perceived barriers), interpersonal factors (family and peer influences) and extra-personal factors (school policy and living arrangement) were identified. Self efficacy was manifested as the strongest influencing factor in most studies. This review highlighted the cultural issues on physical activities of adolescents in Asian countries. Conclusion: This paper provided comprehensive knowledge related to factors influencing physical activity in Asian adolescents. The issue of cultural sensitivity should be considered in the future intervention program designed to improve physical activity of adolescents. Keyword: adolescent, physical activity, health Promotion, Asian countries